Rancang Bangun Aplikasi Analisis pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Layanan Perpustakaan Kota Surabaya - Hafidz, Mohammad Al; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Library of Surabaya government provides the aim of ensuring the service which is always oriented to the satisfaction of the people. For that reason, it needs customer satisfaction measurement procedure. However, Surabaya library has difficulties in processing data, analyzing data, up to the present report. It has an impact on delays and errors in reporting the results of the measurement of customer satisfaction. To overcome these problems, it was made an application as the solution of analyzing the effect of service quality. The process of making the application starts from data processing to determine the value of the variables. The results of the process were analyzed using linear regression method. This method can indicate a causal relationship to know which types of library services affect customer satisfaction. Further analysis of the results can be presented in the form of a report automatically as the results of the analysis of customer satisfaction in Surabaya library. At the implementation phase, this application is used to demonstrate the feasibility of testing the value of 100%. Based on tests on sample data questionnaire in 2012 for public library service, the result showed that service quality influences the customer satisfaction.